SOCIALIZATION OF FINANCING SUPPORT IN AN EFFORT TO EMPOWER MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) - Rachmania; Emi Yulia Siska; Titin Hartini; Akbar Sarif (CV. Doki Course and Training, 2023)
Empowerment of UMKMs in the face of intense competition and globalization UMKMs must be able to face global challenges such as expanding marketing horizons, creating innovative products and services, and investing in the development of technology and human resources. This research uses a qualitative approach to the Socialization of Financing Support in Efforts to Empower Micro, Small and Medium Enterprises (